Visa stories : experiences between law and migration - Menozzi, Filippo; Kemal, Bahriye; Mushakavanhu, Tinashe (Cambridge Scholars Publishing, 2013)
Visa Stories: Experiences between Law and Migration is an interdisciplinary volume that addresses recent public controversies on migration in the UK and Europe. In this context, it aims to recover the voice of migrants by proposing a new, non-conventional form of literary writing: the visa narrative genre. This is a versatile and dialogic form which moves beyond strictly academic modes of migration talk and aims to re-introduce a human, experiential dimension in the representation of people o ...